(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
With the help of education, human feelings of contentment, honesty, religion, respect for elders, respect for children are instilled in a person. These qualities increase the human, spiritual and moral potential and social activity of people and accelerate socio-economic development. Reforms in the field of education being carried out in the country, first of all, those who actively participate in the implementation of these reforms, who perfectly master universal values, are healthy, have faith, are mentally deep, morally pure, have their rights, duties and responsibilities. aimed at educating young people who deeply understand their responsibilities.